Phosphorus rather than nitrogen regulates ecosystem carbon dynamics after permafrost thaw - Yang, Guibiao; Peng, Yunfeng; Abbott, Benjamin W.; Biasi, Christina; Wei, Bin; Zhang, Dianye; Wang, Jun; Yu, Jianchun; Li, Fei; Wang, Guanqin; Kou, Dan; Liu, Futing; et al. (Global Change Biology, 2021)
Ecosystem carbon (C) dynamics after permafrost thaw depends on more than just climate change since soil nutrient status may also impact ecosystem C balance. It has been advocated that nitrogen (N) release upon permafrost thaw could promote plant growth and thus offset soil C loss. However, compared with the widely accepted C-N interactions, little is known about the potential role of soil phosphorus (P) availability. We combined 3-year field observations along a thaw sequence (constituted by four thaw stages, i.e., non-collapse and 5, 14, and 22 years since collapse) with an in-situ fertilization experiment (included N and P additions at the level of 10 g N m(-2) year(-1) and 10 g P m(-2) year(-1)) to evaluate ecosystem C-nutrient interactions upon permafrost thaw. We found that changes in soil P availability rather than N availability played an important role in regulating gross primary productivity and net ecosystem productivity along the thaw sequence. The fertilization experiment confirmed that P addition had stronger effects on plant growth than N addition in this permafrost ecosystem. These two lines of evidence highlight the crucial role of soil P availability in altering the trajectory of permafrost C cycle under climate warming.